Relationship between Environmental Factors and Menarche Of 11-14 Year Old Students in Rasht City - Shiva Salehi; Sedigheh Pakseresht; Seyedeh Noshaz Mirhaghjoo; Ehsan KazemnejadLeili (Journal of Holistic Nursing and Midwifery)
Introduction: The process of puberty is one of the most important events of one s life and onset of menstruation (menarche) is one of the important phenomena during the maturation process of females. Undoubtedly, genetics is the main determinant factor in the onset of puberty but several environmental factors contribute to the age of menarche.